2016
DOI: 10.1017/s0954394516000065
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two cities (and one vowel): Sociolinguistic variation in Swedish

Abstract: Previous studies of language contact in multilingual urban neighborhoods in Europe claim the emergence of new varieties spoken by immigrant-background youth. This paper examines the sociolinguistic conditioning of variation in allophones of Swedish /ε:/ of young people of immigrant and nonimmigrant background in Stockholm and Gothenburg. Although speaker background and sex condition the variation, their effects differ in each city. In Stockholm there are no significant social differences and the allophonic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…In other words, they are dropping the allophonic rule in favor of an open pronunciation in all contexts, not just before /r/. However, Gross, Boyd, Leinonen, and Walker's (2016) analysis of recordings made in 2002 showed that the allophonic rule was still used by Gothenburg youth with Swedish-born mothers and that boys in this group had a tendency to a more closed pronunciation in both contexts, although the allophones were kept separate. They also found that the group with the highest degree of variation in the realization of /ε:/ were girls with Swedish-born mothers.…”
Section: Long Vowels In Gothenburg Swedishmentioning
confidence: 97%
See 2 more Smart Citations
“…In other words, they are dropping the allophonic rule in favor of an open pronunciation in all contexts, not just before /r/. However, Gross, Boyd, Leinonen, and Walker's (2016) analysis of recordings made in 2002 showed that the allophonic rule was still used by Gothenburg youth with Swedish-born mothers and that boys in this group had a tendency to a more closed pronunciation in both contexts, although the allophones were kept separate. They also found that the group with the highest degree of variation in the realization of /ε:/ were girls with Swedish-born mothers.…”
Section: Long Vowels In Gothenburg Swedishmentioning
confidence: 97%
“…This sound change is a general tendency in a large part of the country, especially around Gothenburg and Stockholm (Leinonen, 2010). Gross et al (2016) showed that the adaptation of this sound change was most obvious in the speech of youth with foreign-born mothers, where the open [æ:] production was prevalent and the allophonic rule was more rarely applied (Gross et al, 2016).…”
Section: Long Vowels In Gothenburg Swedishmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative hypothesis is that there are differences in the vowel space area. If the alternative hypothesis is corrected as studies from English and other languages suggest (e.g., Labov, 1994;Labov et al, 2006;Boberg, 2008;Gross et al, 2016), we expect significant effects of the variety on the F1 and F2.…”
Section: This Studymentioning
confidence: 92%
“…Stockholm's multiethnolect is part of this linguistic phenomenon that has been exclusively seen (thus far) in cities of European countries that ran postwar guest-worker programs. These include Berlin [2], Copenhagen [3], Gothenburg [4], Hamburg [5], London (Multicultural London English, 'MLE') [6], Malmö [7], Mannheim [8], Oslo [9], Paris [10], Rotterdam [11], and the South Midlands [12].…”
Section: Ethnosocial Dialects Of Europe and Stockholmmentioning
confidence: 99%